2013
DOI: 10.1080/1057610x.2014.853603
|View full text |Cite
|
Sign up to set email alerts
|

The Cyberterrorism Threat: Findings from a Survey of Researchers

Abstract: This article reports on a recent research project exploring academic perspectives on the threat posed by cyberterrorism. The project employed a survey method, which returned 118 responses from researchers working across 24 different countries. The article begins with a brief review of existing literature on this topic, distinguishing between those concerned by the imminent threat of cyberterrorism, and other, more sceptical, views. Following a discussion on method, the article's analysis section then details f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…In the United States (US), according to Allen [7], in December 2013, Target (a departmental store based in Minneapolis) reported that information from more than 110 million credit and debit card payments by its customers were accessed illegally. The hackers stole personal identification numbers (PINs) from the cards, and as a result, Target lost more than $3.5 billion [8]. Hutchings [9] cited that Neiman Marcus (a Dallas based retail store) also reported that the information from 1.1 million credit and debit card payments was hacked in 2013.…”
Section: Hacking Incidentsmentioning
confidence: 99%
“…In the United States (US), according to Allen [7], in December 2013, Target (a departmental store based in Minneapolis) reported that information from more than 110 million credit and debit card payments by its customers were accessed illegally. The hackers stole personal identification numbers (PINs) from the cards, and as a result, Target lost more than $3.5 billion [8]. Hutchings [9] cited that Neiman Marcus (a Dallas based retail store) also reported that the information from 1.1 million credit and debit card payments was hacked in 2013.…”
Section: Hacking Incidentsmentioning
confidence: 99%
“…Selain itu, pembentukan pasukan cyber beserta teknologi-teknologi pertahanan cyber juga menjadi sangat vital mengingat potensi serangan cyber semakin meningkat. Kelompokkelompok terror juga kerap kali memanfaatkan teknologi komunikasi dan informasi seperti internet dalam melakukan aktifitasnya (Andreas & Naím, 2012;Blaker, 2015;Heickerö, 2014;Jarvis et al, 2014;Sultan, 2018;Ward, 2018).…”
Section: Analisis Dan Pembahasanunclassified
“…In a study of academic opinion around cyberterrorism, Jarvis, Macdonald, and Nouri identified "considerable disagreement" regarding the "extent to which this phenomenon poses a security threat." 39 Simplifying, they characterize this disagreement as a debate between "the concerned" and "the sceptics"for whom cyberterrorism remains little more than a hyperbolic media construction. Heickerö dichotomizes this debate similarly between those who view the cyberterrorist threat as "real and considerable," and others for whom there is 'no threat at all or only a very limited one."…”
Section: Assessing the Cyberterrorism Threatmentioning
confidence: 99%